Identifikasi Mikroalga sebagai Indikator Pencemaran Lingkungan Air di Perairan Sungai Umala Ogena Kota Baubau - Yustika Sari; Muhammad Iksan; Agus Slamet (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2021)
The Umala Ogena River is one of the most famous waterways in Baubau City. During the Sultanate, this river was the economic lifeblood of the Buton people. Rivers are used for various purposes, including transportation, bathing, and washing. If the river ecology is disturbed, all living organisms that exist will be threatened with extinction. Water pollution is the entry of living things, chemicals, energy, or other components into water, thereby reducing water quality. Phytoplankton are microscopic creatures that live on the surface of the water and are classified as plants. The Umala Ogena River is in a mild to moderate polluted phase with organic and inorganic pollutants. This occurs as a result of polluting chemicals found in domestic sewage polluting waterways.